2004
DOI: 10.1023/b:bebm.0000035121.85533.08
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional State of Rat Ovaries in Early and Late Periods after Administration of Platinum Cytostatics

Abstract: Experiments on Wistar rats showed that cisplatin and carboplatin induced similar morphological alterations in the ovaries. Both agents reduced the number of structural and functional elements, but the effect of cisplatin was more pronounced. Morphological changes observed in the early period after injection of the preparations were accompanied by prolongation of the estrous cycle, which was longer in rats treated with carboplatin. Partial and reversible sterility was observed in females at the early terms afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…As for the effects of CDDP on rat ovary, decreases in primordial follicles and Müllerian inhibiting substance, which is produced by the primordial and small ovarian follicles, were observed after a single dose of CDDP (Borovskaya et al, 2004;Yucebilgin et al, 2004;Yeh et al, 2006). Repeated dosing of CDDP during 1 or 2 estrous cycles in rats induces a decrease in the total number of follicles and large follicles are more sensitive to the toxic effects of CDDP than small follicles (Shinagawa, 1998;Matsuo et al, 2007).…”
Section: Sp77mentioning
confidence: 99%
“…As for the effects of CDDP on rat ovary, decreases in primordial follicles and Müllerian inhibiting substance, which is produced by the primordial and small ovarian follicles, were observed after a single dose of CDDP (Borovskaya et al, 2004;Yucebilgin et al, 2004;Yeh et al, 2006). Repeated dosing of CDDP during 1 or 2 estrous cycles in rats induces a decrease in the total number of follicles and large follicles are more sensitive to the toxic effects of CDDP than small follicles (Shinagawa, 1998;Matsuo et al, 2007).…”
Section: Sp77mentioning
confidence: 99%
“…In rats, cisplatin has previously been shown to cause damage to the ovaries by increasing the percentage of follicular apoptosis and follicular cyst formation in rats. 6,7 In animal models, several studies have been performed on the effects of cisplatin administration during pregnancy. Administration of cisplatin during pregnancy in mice and rats resulted in fetal mitochondrial toxicity, DNA adduct formation, and increased incidence of tumors of kidney, skin, lung and other organs.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that chemotherapeutic medicines leading to either temporary or permanent infertility severely affected the ovaries and hormonal balance (DeVita et al 2005). In rats, CDDP has been shown to cause ovarian damage, at varying degrees ranging from minimal effects to ovarian failure, increased follicular apoptosis, decreased expression anti-Müllerian hormone (AMH), alterations in the estrous cycle, and a decrease in the number of AMH-producing follicles (Borovskaya et al 2004;Yucebilgin et al 2004;Yeh et al 2006Yeh et al , 2008. Our study has demonstrated that CDDP caused significant toxicity in the ovarian tissues of rats.…”
Section: Discussionmentioning
confidence: 68%